Peran Teknologi Informasi dalam Memoderasi Pengaruh Transparansi dan Akuntabilitas Biaya Pendidikan terhadap Persepsi Mahasiswa - Hurian Kamela (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – This study aims to analyze the influence of transparency and accountability in education cost management on student perceptions and to examine the moderating role of information technology utilization in this relationship. Methods – This study employed a quantitative approach using a survey method. The population consisted of active students from several higher education institutions in the Jabodetabek area, with 247 respondents selected through purposive sampling. Data was analyzed using moderated regression to examine the direct effects of transparency and accountability on student perceptions and to test the moderating role of information technology utilization. Findings – The results indicate that transparency and accountability in the management of education costs have a positive and significant effect on student perceptions. Furthermore, the utilization of information technology significantly strengthens the relationship between transparency and student perceptions, as well as between accountability and student perceptions. These findings suggest that technology-based information systems play a crucial role in enhancing students’ understanding, trust, and acceptance of education cost management practices. The moderation results show significance values of 0.009 and 0.003, indicating that both moderating hypotheses are accepted. This confirms the importance of information technology in supporting transparency and the management of student-related educational costs.Research Implications – This study shows that transparency and accountability in educational costs significantly influence student perceptions. Practically, universities need to provide clear, open, and easily accessible financial information. The use of digital technology should be optimized to support transparent and real-time cost reporting. These efforts can strengthen student trust and improve institutional credibility.